Abram Allen homeplace in Davie County, 1942. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 4-26-42 p. 14.
Abram Allen homeplace in Davie County, 1942. The children are: Cornell, C. W., and Lester Reece, and Leta Gray Allen.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth